JUSTICE AND LEGAL RECOGNITION OF INTERFAITH HEIRS IN INDONESIA INHERITANCE LAW - Tri Andari Dahlan; Ubaidillah Kamal; Yustina Dhian Novita; Risky Agung Firnanda; Aldina Ulya (Contemporary Issues on Interfaith Law and Society, 2026)
The pluralistic inheritance law system in Indonesia, which consists of Islamic inheritance law, Western civil inheritance law, and customary inheritance law, creates significant legal complexity, particularly in inheritance disputes involving differences of religion between the deceased and the heirs. Normatively, Islamic inheritance law does not recognize interfaith inheritance, while Western civil law adopts a principle of religious neutrality, and customary law varies according to each community’s kinship system. These differences result in unequal legal protection for interfaith heirs and raise serious issues regarding legal certainty and substantive justice. This research aims to analyze the legal position of interfaith heirs within Indonesia’s inheritance law system and to examine how the concept of justice is realized in judicial practice, particularly through the application of the concept of wasiat wajibah (mandatory bequest). This study employs a normative juridical method using statutory, conceptual, and jurisprudential approaches. The findings demonstrate that Western civil inheritance law consistently recognizes inheritance rights without considering religious differences. In contrast, Islamic inheritance law normatively prohibits interfaith inheritance; however, judicial practice has developed the application of wasiat wajibah as a legal compromise to protect the economic interests of non-Muslim heirs of Muslim descendants. Nevertheless, the application of wasiat wajibah remains inconsistent and highly dependent on judicial discretion, resulting in legal uncertainty and unequal treatment in similar cases. This research concludes that the current pluralistic inheritance framework has not yet fully guaranteed legal certainty and substantive justice for interfaith heirs. Therefore, it recommends the harmonization and reformulation of national inheritance law to establish clearer and more uniform normative guidelines. Such reform is necessary to ensure the realization of legal certainty, social utility, and substantive justice while remaining aligned with religious values and the multicultural character of Indonesian society.